Developing Children's Observation Skills Using a Fractal Pattern from Nature. (3rd April 2019) - Yurumezoglu, Kemal; Oztas Cin, Merve
Abstract: This study aimed to support the development of the scientific observation skills of children at an early age using a pattern selected from nearby nature. For this purpose, a simple, innovative and authentic observation activity was designed using thorny burnet ( Sarcopoterium spinosum L.), a plant unique to the Mediterranean region. The activity was conducted in a preschool institution with six-year-old children in the class hours of a weekly science course in three different environments (in-class, out-of-class, and out-of-school), and seven stages. In this activity, which aimed to transform children's natural/spontaneous observation skills into scientific observation skills, patterns were revealed through systematic and sequential observation and drawings. At the end of the activity, it was found that the children had developed skills related to breaking a whole into its parts and putting the parts together according to patterns, making detailed observations, and systematic data collection, and they successfully implemented these skills outside the classroom and school.